Maternal, Obstetric, and Neonatal Characteristics Associated with Delayed Cord Clamping - Zhao, Emily; Valcarcel, Breanna; Shantz, Camille; Meiss, Lauren; Xie, Siwei; Tackett, Sean; Schwarz, Brittany; Rosner, Mara (American Journal of Perinatology)
Objective To evaluate the factors associated with completed delayed cord clamping (DCC). Study Design We conducted a retrospective review of viable singleton deliveries at a single academic medical center from January 1, 2020-Dec 31, 2022. Demographics, obstetric variables, and neonatal data were extracted from the electronic medical record. Patients who received DCC were compared to those who did not. Multivariate logistic regression was used to assess factors associated with completion of 30-60 seconds of DCC, with a sub-analysis of preterm deliveries < 30 weeks. Results DCC was completed in 5018/5889 (85.2%) eligible deliveries. Lower DCC rates were observed among non Black, White, or Asian patients vs White patients (82.1% vs 87.1%; adjusted odds ratio [aOR] 0.60, 95% CI 0.47-0.78) and in 2020 vs 2022 (83.6% vs 86.5%; aOR 0.74, 95% CI 0.61-0.91). Patients who completed DCC had lower mean BMI (32.59 vs 34.53, aOR 0.99, 95% CI 0.98-0.996), were less likely to be nulliparous (83.9% vs 86.4%, aOR 0.78, 95% CI 0.66-0.92), less likely to have pregestational diabetes (72.8% vs 86.1%, aOR 0.63, 95% CI 0.45-0.87), chorioamnionitis (72.9% vs 85.6%, aOR 0.51, 95% CI 0.36-0.73), or postpartum hemorrhage (73.0% vs 85.6%, aOR 0.59, 95% CI 0.41-0.86). Preterm (68.5% vs 87.8%, aOR 0.50, 95% CI 0.40-0.63) and cesarean deliveries (77.2% vs 90.0%, aOR 0.72, 95% CI 0.60-0.85), and infants requiring resuscitation (61.7% vs 91.6%; aOR 0.20, 95% CI 0.17-0.23) were less likely to have completed DCC. Among preterm newborns < 30 weeks, neonatal resuscitation was the only factor associated with not receiving DCC after adjustment. Conclusion Race, delivery mode and year, maternal BMI, nulliparity, pregestational diabetes, chorioamnionitis, postpartum hemorrhage, preterm birth, and neonatal resuscitation were independently associated with completed DCC. Strategies to improve DCC execution should target preterm infants and address the challenges of performing DCC in neonates requiring urgent resuscitation.